A Systematic Review of Dynamic Reconfiguration of Software Projects - Callegari, Daniel Antonio; Bastos, Ricardo Melo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2008: Anais do XXII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2008.21339, 2008)
Software companies often make use of project management knowledge as well as a set of development processes in order to build their solutions with quality and within scope, time and resource constraints. Software projects are very dynamic systems that demand recurrent adjustments of their plans even during execution due to their particular nature. Such adjustments can be viewed as reconfigurations on schedule, on resource allocation and on other project elements. A systematic review is a means of evaluating and interpreting all available research relevant to a particular area of interest. This paper presents the results from a systematic review of four subareas underlying the dynamic reconfiguration of software projects. A number of works were analyzed from the year of 2004 up to the present moment.